Safety and efficacy of recombinant newcastle disease virus expressing human interleukin-12 as a potential vaccine in breast cancer - Mohamed Amin, Zahiah (2019)
In this developing era, breast cancer still remains a life-threatening disease globally. However, oncolytic virotherapy has taken over interest as a promising non-conventional alternative to treating breast cancers. Newcastle disease virus (NDV), an avian paramyxovirus has been demonstrated with significant oncolytic activity against cancer based on numerous preclinical studies. Today, genetically modified viruses coding for immunomodulatory agents, such as cytokines or chemokines, have come into focus. Such engineered viruses are able to promote efficient immune responses against tumour cells. The overall of this project aims to study the effects of a recombinant NDV expressing human interleukin 12 (rAF-IL12) in the apoptotic and metastatic process in MCF7 and MDA-MB231 human breast cancer cell lines. The parental NDV AF2240 was used as a positive control in this study. Notably, rAF-IL12 was able to maintain its stability when passaged in specific pathogen free (SPF) eggs up to ten passages. Furthermore it is considered safe as it selectively induced cytotoxic effects in chicken and breast cancer cell lines while sparing non-cancerous breast cell line as demonstrated through the MTT assay. The stability of each passaged rAF-IL12 was verified via haemagglutination assay (HA), mean death time (MDT) and intracerebral pathogenicity index (ICPI), while the IL12 was quantified through Enzyme-Linked Immunosorbent Assay (ELISA). Comparable to AF2240, rAF-IL12 was also able to induce apoptosis significantly based on several apoptotic assays. Both rAF-IL12 and AF2240 managed to increase the percentage of G2/M and S phase in the cell cycle analysis while inducing the percentage of apoptosis. Although both AF2240 and rAF-IL12 demonstrated comparable in vitro apoptosis results, rAF-IL12 possessed significant (p<0.05) antimetastatic activity in comparison to AF2240 based on metastasis related assays including the in vitro scratch assay, migration/ invasion assay, human umbilical vein endothelial cell (HUVEC) tube formation and rat aortic ring assay. Additionally, to further evaluate the anti-tumour and anti-metastatic mechanism of rAF-IL12, in vivo studies were conducted using 4T1-challenged BALB/c mice as a model of this study. The rAF-IL12 was proven to function as an improved tumour vaccine as it significantly (p<0.05) reduced the size of tumour in comparison to the parental AF2240 virus. Apoptotic results showed that the number of cancer cells in the tumour significantly (p<0.05) reduced after 28 days of intra-tumoural treatment with rAF-IL12 (27 HAU). In addition, rAF-IL12 was able to inhibit the migration of cancer cells to other vital organs as opposed to the untreated group. To further elucidate the apoptotic and anti-metastatic mechanism of rAF-IL12 at molecular level, NanoString nCounter was conducted. Even though both AF2240 and rAF-IL12 exhibited similar mechanism of action, rAF-IL12 was more potent than AF2240 in terms of apoptosis and anti- metastasis activity. In conclusion, both rAF-IL12 and AF2240 were able to inhibit the proliferation of breast cancer cells and induce apoptosis in the in vitro studies; however, rAF-IL12 was able to demonstrate significant (p<0.05) improved functionality in comparison to AF2240 alone based on the in vivo studies. This proved that interleukin 12 was able to increase the immune response against tumour cells by inducing cell death, anti-angiogenesis and anti-metastasis effects, further improving the function of AF2240 as a potential vaccine in breast cancer.